Growth, growth fluctuations, and the stages of technological advance - Hans H. Glismann; Ernst-Jürgen Horn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
It is a well-established tradition to define the subject before embarking on an investigation. In our case, definition is to be concerned with economic development and scientific-technical progress. The former poses no problem in the economist's profession. According to Mirabeau, every moral or physical advance can be grasped by one indicator, which he called the net product. Today, Mirabeau would probably encounter objections as far as the measurement of moral progress by the net product is concerned, although some would argue that also today morals, as well as gods, are always with the winners. Anyhow, real changes in the availability of goods and services is, according to national and international standards, measured by changes in real net social product; conceptual problems - e.g., of how to treat the non-pecuniary costs (environmental pollution) and benefits (value added of housewives) - are, of course, part of every measurement. What matters here is that the approach as such is hardly controversial.
Keywords: 330